High prevalence of falls, fear of falling, and impaired balance in older adults with pain in the United States: findings from the 2011 National Health and Aging Trends Study. - Patel, K; Phelan, E; Leveille, S; Lamb, S; Missikpode, C; Wallace, R; Guralnik, J; Turk, D (Blackwell Publishing Inc., 2014)
OBJECTIVES: To determine the prevalence of clinically relevant falls-related outcomes according to pain status in older adults in the United States. DESIGN: Cross-sectional analysis of the 2011 National Health and Aging Trends Study, a sample of Medicare enrollees aged 65 and older (response rate 71.0%). SETTING: In-person assessments were conducted in the home or residential care facility of the sampled study participant. PARTICIPANTS: Individuals aged 65 and older (n = 7,601, representing 35.3 million Medicare beneficiaries). MEASUREMENTS: Participants were asked whether they had been "bothered by pain" and the location of pain, as well as questions about balance and coordination, fear of falling, and falls. RESULTS: Fifty-three percent of the participants reported bothersome pain. The prevalence of recurrent falls in the past year (≥ 2 falls) was 19.5% in participants with pain and 7.4% in those without (age- and sex-adjusted prevalence ratio (PR) = 2.63, 95% confidence interval (CI) = 2.28-3.05). The prevalence of fear of falling that limits activity was 18.0% in those with pain and 4.4% in those without (adjusted PR = 3.98, 95% CI = 3.24-4.87). Prevalence of balance and falls outcomes increased with number of pain sites. For example, prevalence of problems with balance and coordination that limited activity was 6.6% in participants with no pain, 11.6% in those with one site of pain, 17.7% in those with two sites, 25.0% in those with three sites, and 41.4% in those with four or more sites (P < .001 for trend). Associations were robust to adjustment for several potential confounders, including cognitive and physical performance. CONCLUSION: Falls-related outcomes were substantially more common in older adults with pain than in those without. Accordingly, pain management strategies should be developed and evaluated for falls prevention.